2018
DOI: 10.1371/journal.pgen.1007324
|View full text |Cite
|
Sign up to set email alerts
|

High mutation rates limit evolutionary adaptation in Escherichia coli

Abstract: Mutation is fundamental to evolution, because it generates the genetic variation on which selection can act. In nature, genetic changes often increase the mutation rate in systems that range from viruses and bacteria to human tumors. Such an increase promotes the accumulation of frequent deleterious or neutral alleles, but it can also increase the chances that a population acquires rare beneficial alleles. Here, we study how up to 100-fold increases in Escherichia coli’s genomic mutation rate affect adaptive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 123 publications
4
95
0
Order By: Relevance
“…This indicates that multiple mutators emerged either simultaneously or sequentially and that nonmutator clones coexisted with both strong hypermutators (mutation rates up to 1,200-fold higher than the ancestral) and with intermediate hypermutators (10-to 100-fold increases in mutation rate). Coexistence between clones differing in mutation rate by less than 70-fold has been previously observed [42][43][44][45]. However, to the best of our knowledge, our results represent the first observation of long-term coexistence (>1,000 generations, i.e., >54 days) of clones differing in mutation rate by around 1,000-fold in the gut.…”
Section: Emergence and Maintenance Of Mutation Rate Variation In A Gusupporting
confidence: 77%
See 1 more Smart Citation
“…This indicates that multiple mutators emerged either simultaneously or sequentially and that nonmutator clones coexisted with both strong hypermutators (mutation rates up to 1,200-fold higher than the ancestral) and with intermediate hypermutators (10-to 100-fold increases in mutation rate). Coexistence between clones differing in mutation rate by less than 70-fold has been previously observed [42][43][44][45]. However, to the best of our knowledge, our results represent the first observation of long-term coexistence (>1,000 generations, i.e., >54 days) of clones differing in mutation rate by around 1,000-fold in the gut.…”
Section: Emergence and Maintenance Of Mutation Rate Variation In A Gusupporting
confidence: 77%
“…TCG) and measured their mutation rates. We generated approximately 20 clones carrying the DnaQ L145P allele, as dnaQ hypermutators can exhibit high mutation rate variation, possibly because of the rapid emergence of suppressors [42,51]. The dnaQ clones indeed showed a very high mutation rate, reaching 3,000-fold increases for both nalidixic acid and rifampicin ( Fig 2C).…”
Section: Mutations In the Proofreading And Catalytic Subunits Of Dnamentioning
confidence: 96%
“…However, mutation rate estimates hold several uncertainties. For example, laboratory conditions may not resemble generation times in nature (40,41) or disregard factors such as differential mutation rates among strains, selection, recombination, and mutational bias (41,42). Furthermore, little is known on how environmental factors, ecological niches, or different host species affect the rates of accumulation of diversity (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…KEYWORDS Pseudomonas aeruginosa, antimicrobial agents, bacterial evolution, ceftazidime-avibactam, host-pathogen interactions, hypermutator, microbial genomics, mismatch repair I n general, the maintenance of high-fidelity DNA replication and the reduction of spontaneous mutation rates are beneficial to organisms. Previous work has demonstrated that even moderately elevated mutational rates may be substantially deleterious and that exceeding certain threshold mutational rates results in the irrecoverable loss of essential wild-type sequences and population collapse (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Replication fidelity in bacteria is maintained by elaborate machinery that includes the proofreading exonucleases in replicative DNA polymerases and an array of DNA repair proteins broadly organized into homologous DNA recombination, base and nucleotide excision repair pathways, and methyl-directed mismatch repair (MMR) (11)(12)(13).…”
mentioning
confidence: 99%